Pengaruh Profesionalisme, Etika Profesi, Pengetahuan, Dan Pengalaman, Terhadap Pertimbangan Tingkat Materialitas - Haqqoe, Dwi Atmo Abu Rizza, Drs. Agus Endro Suwarno, M.Si (2017)
This research aims to provide empirical evidence of the influence of: the influence of professionalism, professional ethics, knowledge and pengalaman against materialitas level considerations. Sample collection method using the technique of convenience sampling. This research is done by using the primary data. The population in this research is the auditor on Public Accountant in Central Java and Yogyakarta. The analysis method used is multiple regression analysis. The results of this research prove that the variables professionalism and knowledge affect materialitas level considerations, while the variables professional ethics and experience did not influence the level of materialitas considerations.